2010
DOI: 10.2353/jmoldx.2010.090187
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Molecular Classification of Renal Tumors Using MicroRNA Expression

Abstract: Subtypes of renal tumors have different genetic backgrounds, prognoses, and responses to surgical and medical treatment, and their differential diagnosis is a frequent challenge for pathologists. New biomarkers can help improve the diagnosis and hence the management of renal cancer patients. We extracted RNA from 71 formalin-fixed paraffin-embedded (FFPE) renal tumor samples and measured expression of more than 900 microRNAs using custom microarrays. Clustering revealed similarity in microRNA expression betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 54 publications
7
76
0
1
Order By: Relevance
“…In consistence with previous studies (15,39), no significant correlation was identified between miR-141 expression and RCC tumor stage, grade, or size. Recent reports have also showed the ability of miRNAs to distinguish between RCC subtypes with an accuracy of about 90%, including ccRCC, papillary RCC (pRCC), chRCC, and the closely related benign tumor oncocytoma (40,41). Here, miR-141 expression was equally decreased in malignant (ccRCC, chRCC, and sarcoma RCC) and benign renal tumors (AML).…”
Section: Discussionmentioning
confidence: 70%
“…In consistence with previous studies (15,39), no significant correlation was identified between miR-141 expression and RCC tumor stage, grade, or size. Recent reports have also showed the ability of miRNAs to distinguish between RCC subtypes with an accuracy of about 90%, including ccRCC, papillary RCC (pRCC), chRCC, and the closely related benign tumor oncocytoma (40,41). Here, miR-141 expression was equally decreased in malignant (ccRCC, chRCC, and sarcoma RCC) and benign renal tumors (AML).…”
Section: Discussionmentioning
confidence: 70%
“…The cluster of similar miRNAs in benign and malignant follicular tumors displaying Hürthle cell features supports also the assumption that such features represent a phenotype that is superimposed on different oncogenic genotypes. This assumption is further reinforced by the upregulation of miR-221 in renal oncocytomas (Fridman et al 2010; Table 3). …”
Section: Microrna Alterations In Hü Rthle Cell Tumorsmentioning
confidence: 89%
“…Similarly, miR-204 loss enhanced migration and stem cell phenotype in vivo (37 ). MiR-139 expression was shown to differ between different kidney cancer subtypes (38 ) and was also linked to metastasis and prognosis in ccRCC (39 ). In our network, miR-139 targets ETS1, TCF4, ZEB1, and CCND2.…”
Section: Discussionmentioning
confidence: 93%